2019
DOI: 10.1136/bjophthalmol-2018-313702
|View full text |Cite
|
Sign up to set email alerts
|

Extensive circumferential partial-thickness sclerectomy in eyes with extreme nanophthalmos and spontaneous uveal effusion

Abstract: AimTo describe an extensive scleral excision technique to treat uveal effusion in nanophthalmic eyes.MethodsThis prospective, interventional series of eight eyes of five consecutive patients with nanophthalmos underwent scleral window surgeries. Ninety per cent of the scleral thickness, extending from immediately behind the extraocular muscle insertions to the vortex veins for 3 and 1/4 quadrants, was removed. The main outcome measure was resolution of the uveal effusions.ResultsEight eyes of five patients (on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 34 publications
1
22
0
Order By: Relevance
“…Many of their cases were firstly misdiagnosed as choroidal melanoma (47%), choroidal metastasis (3%), choroidal tumor nonspecified (34%) and only 16% was diagnosed correctly as UES [10]. In type 1 UES, 65% of the cases eventually become bilateral, which is the case with our patient [11].…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…Many of their cases were firstly misdiagnosed as choroidal melanoma (47%), choroidal metastasis (3%), choroidal tumor nonspecified (34%) and only 16% was diagnosed correctly as UES [10]. In type 1 UES, 65% of the cases eventually become bilateral, which is the case with our patient [11].…”
Section: Discussionmentioning
confidence: 53%
“…The most commonly used treatment is surgery involving the creation of surgical sclerostomies (scleral window surgery) or partial thickness sclerectomies to support transscleral drainage [1,8,9]. In some cases, steroids or NSAID may be effective [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…The resistance of the transscleral sclera to protein movement decreases after sclerectomy, although this may be affected by the amount of sclera excised and postoperative fibrous scarring [ 63 ]. A prospective study showed that partial quadrant PTS (90% of the scleral thickness) in nanophthalmic eyes with UES had a significant effect [ 64 ], and PTS produced better results in the four quadrants [ 65 ]. The authors of the study considered that the PTS performed in the four quadrants could reduce the overall resistance to subchoroidal fluid outflow, thereby promoting the outflow of fluids in the suprachoroidal and subretinal spaces [ 64 , 65 ].…”
Section: Treatments For Uveal Effusion Syndrome In Nanophthalmic Ementioning
confidence: 99%
“…A prospective study showed that partial quadrant PTS (90% of the scleral thickness) in nanophthalmic eyes with UES had a significant effect [ 64 ], and PTS produced better results in the four quadrants [ 65 ]. The authors of the study considered that the PTS performed in the four quadrants could reduce the overall resistance to subchoroidal fluid outflow, thereby promoting the outflow of fluids in the suprachoroidal and subretinal spaces [ 64 , 65 ]. However, due to the large area of sclera removed, current technology may cause dilation of the sclera [ 64 ].…”
Section: Treatments For Uveal Effusion Syndrome In Nanophthalmic Ementioning
confidence: 99%
See 1 more Smart Citation